2016
DOI: 10.2460/javma.248.6.673
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmic variables in rehabilitated juvenile Kemp's ridley sea turtles (Lepidochelys kempii)

Abstract: Results provided preliminary reference ranges for objective assessment of ophthalmic variables in healthy juvenile Kemp's ridley sea turtles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
3
1
Order By: Relevance
“…The corneal thickness and the anterior chamber depth of the animals in this study were larger than what was found by Gornik et al [10] for juvenile Kemp's ridley sea turtles (Lepidochelys kempii) using optical coherence tomography. Lower values for these structures were also found in frozen eyes of Chelonia mydas, Dermochelys coriacea and E. imbricata [31].…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…The corneal thickness and the anterior chamber depth of the animals in this study were larger than what was found by Gornik et al [10] for juvenile Kemp's ridley sea turtles (Lepidochelys kempii) using optical coherence tomography. Lower values for these structures were also found in frozen eyes of Chelonia mydas, Dermochelys coriacea and E. imbricata [31].…”
Section: Discussioncontrasting
confidence: 77%
“…Several ultrasonographic studies have been performed on sea turtles to evaluate the coelomic cavity [ 25 ], but to the authors’ knowledge, there are no reports on ophthalmic echobiometry in these species. However, the increasing number of sea turtles in conservation centres [ 14 ], and considering studies on ophthalmic diseases in these species [ 10 , 12 15 ], there is rising concern among institutions and staff about the conservation of vision in these animals, to promote quality of life and allow for the possibility of reintroduction into a free living environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to its established clinical applications in humans, SD‐OCT has been used in veterinary ophthalmology to visualise the cornea and anterior segment of a diverse range of species, including domestic dogs and cats, turtles and horses . The development of rodent‐adapted OCT technology has greatly improved the accessibility and quantitation of anterior segment imaging in small animal models of ocular inflammation, of which mice and rats are the most commonly used species.…”
Section: As‐oct Imaging In Animalsmentioning
confidence: 99%